2019
DOI: 10.1021/acs.jced.8b00944
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing Vitamin E Molecularly Imprinted Polymers via Precipitation Polymerization

Abstract: Molecularly imprinted polymers (MIPs) were prepared by the precipitation polymerization process, with vitamin E as the template molecule, ethylene glycol dimethacrylate as the cross-linker, and three different functional monomers, respectively. Adsorption experiments were conducted to investigate the performance of each MIP and compared to the nonimprinted polymers (NIPs). It was found that MIPs are superior to NIPs in general, with acrylamide-based MIP showing the best adsorption capacity of 38.8 mg·g–1 and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…The SEM analysis shows that spherical particles were obtained with a diameter of around 0.2 µm for the MIPs, while an interconnected-irregular bulk was observed in the NIPs. This morphological characterization shows the successful synthesis of MIPs and further proves by Lu et al [60] revealed that MIP particles were spherical and well dispersed. The morphology of MIP AM synthesized at various crosslinkers is illustrated in Figure 8.…”
Section: Characterization Of Molecularly Imprinted Polymersupporting
confidence: 72%
See 1 more Smart Citation
“…The SEM analysis shows that spherical particles were obtained with a diameter of around 0.2 µm for the MIPs, while an interconnected-irregular bulk was observed in the NIPs. This morphological characterization shows the successful synthesis of MIPs and further proves by Lu et al [60] revealed that MIP particles were spherical and well dispersed. The morphology of MIP AM synthesized at various crosslinkers is illustrated in Figure 8.…”
Section: Characterization Of Molecularly Imprinted Polymersupporting
confidence: 72%
“…Lu et al [60] observed peaks (Figure 12) at 1150 cm −1 may be related to the vibration of the C-O bond stretching in EGDMA (a). Peaks at 3400 cm −1 correspond to -NH groups, 1637 cm −1 to the stretching vibration of the C=C double bond, and 1720 cm −1 to the stretching vibration of C=O groups, respectively, in AM (b).…”
Section: Characterization Of Molecularly Imprinted Polymermentioning
confidence: 98%
“…Iridoid glycosides, spiramycin, 2,4-dichlorophenoxyacetic acid, diclofenac, alfatoxins [17][18][19][20][21] Suspension polymerization Malachite green, p-hydroxybenzoic acid, timolol, alfatoxins B1, Pb 2+ [22][23][24][25][26] Emulsion polymerization Quercetin, malachite green, Listeria monocytogenes, triazines, Cd 2+ [27][28][29][30][31] Seed polymerization Nicotinamide, bisphenol A, promazine derivates [32][33][34] Precipitation polymerization Triclosan and triclocarban, strychnine, caffeic acid, vitamin E, prednisolone [35][36][37][38][39] RAFT polymerization Benzimidazole, propranolol, polycyclic aromatic hydrocarbons [40][41][42] Atom transfer radical polymerization Ofloxacin, ␤2-agonists [43,44] Sol-gel Iprodione, methylxanthines [45,46] RAFT: Reversible addition fragmentation chain transfer.…”
Section: Bulk Polymerizationmentioning
confidence: 99%
“…The average particle size of MIPs was about 400 nm while the average particle size of spherical NIPs was 800 nm, which indicated that the template could affect the particle size. Subsequently, precipitation polymerization was employed to prepare many spherical MIPs for selective recognition of tetracycline, 26 vitamin E, 27 etc. The key point of this method was the solubility and amount of solvent.…”
Section: Spherical Mips By Precipitation Polymerizationmentioning
confidence: 99%